Contribution of vitamin D receptor genotypes to bone mineral density in young male athletes with different impact loading - Nakamura, O.; Ishii, T.; Mankyu, H.; Tsubakimoto, S.; Nomura, T.; Tokuyama, K. (European Journal of Sport Science, 2002)
Bone adaptation to exercise relies on exposures to impact loading in sports, but the ability of skeletal change seems to be highly variable among individuals. The present study was designed to investigate the association between a polymorphism in the vitamin D receptor (VDR) gene at the translation initiation site and impact loading on bone mineral density (BMD). Analysis of the VDR genotypes detected by endonuclease FokI (FF, Ff, and ff) and measurement of total body BMD (TBMD) were performed in 212 young males; 84 athletes were involved in weight-bearing sports, 48 in competitive swimming, and 80 non-athletic controls. The differences in TBMD between athletes and controls depended on the VDR genotypes; enhanced BMD in weight-bearing athletes was found in FF (7.7%, p < .01 as compared with the genotype-matched control) and Ff (6.9%, p < .01) but not in ff (1.8%, p = .60). When swimmers were compared with VDR genotype-matched controls, lower TBMD was observed only in FF (-4.5%, p < .05). These findings imply a new notion that the FF genotype appears to respond more sensitively to difference in impact loading in regulating TBMD rather than being a predictor of high BMD in sedentary individuals as shown in previous reports.